Training of modern circumsision with super ring method on circumcision practices in Banjar District, South Kalimantan - Irfan Maulana; Ida Yuliana; Heryyanoor Heryyanoor; M. Noor Ifansyah; Andri Suwarno; Lutfi Aulia Rahman; Nanang Saputro Agung (Community Empowerment, 2022)
Circumcision is better known as khitan or Indonesian people often call it sunat. Circumcision is usually performed for a specific purpose and has religious and medical benefits. Circumcision even though minor surgical procedures have been carried out with the correct technique and guaranteed sterility, complications of the procedure will still exist. Complications that occur are influenced by experience, skills, and techniques and tools used by circumcision practitioners. For this purpose, community service program in the form of modern circumcision training using the ring method were carried out for 11 circumcision practitioners in the Banjar Regency area. The methods used are question and answer lectures, demonstrations, FGDs, and the practice of performing circumcision on patients with the assistance and supervision of instructors. The result of this program is an increase in understanding and skills in performing modern super ring circumcision, a combination of anesthetic techniques without a needle, and producing entrepreneurs in this field.